Microprocessor mediates transcriptional termination of long noncoding RNA transcripts hosting microRNAs - Dhir, Ashish; Dhir, Somdutta; Proudfoot, Nick J.; Jopling, Catherine L. (Nature Publishing Group, 2015)
MicroRNA (miRNA) play a major role in the post-transcriptional regulation of gene expression. Mammalian miRNA biogenesis begins with co-transcriptional cleavage of RNA polymerase II (Pol II) transcripts by the Microprocessor complex. While most miRNA are located within introns of protein coding genes, a substantial minority of miRNA originate from long non coding (lnc) RNA where transcript processing is largely uncharacterized. Here, by detailed characterization of liver-specific lnc-pri-miR-122 and genome-wide analysis, we show that most lnc-pri-miRNA do not use the canonical cleavage and polyadenylation (CPA) pathway but instead use Microprocessor cleavage to terminate transcription. Microprocessor inactivation leads to extensive transcriptional readthrough of lnc-pri-miRNA and transcriptional interference with downstream genes. Consequently we define a novel RNase III-mediated, polyadenylation-independent mechanism of Pol II transcription termination in mammalian cells.